Формування та досвід використання педагогічних умов забезпечення якості професійної підготовки майбутніх інженерів-програмістів у Національному технічному університеті "ХПІ" - Романовський, Олександр Георгійович; Гончаренко, Тетяна Євгенівна (Класичний приватний університет, 2016)
У статті розглянуто процес формування педагогічних умов, що сприяють якісній професійній підготовці майбутніх програмістів, а також досвід упровадження визначених педагогічних умов у навчальний процес кафедри ПІІТУ НТУ "ХПІ". Найбільш вагомими педагогічними умовами для підготовки фахівців з програмної інженерії визначено формування англомовного потоку, добре знання студентами комп’ютерної прикладної математики, досвід роботи в реальних ІТ-проектах викладачів комп’ютерних дисциплін, створення на території ВНЗ навчально-науково-виробничих комплексів, створення конкурентного середовища в групах студентів майбутніх програмістів і впровадження дуального підходу в навчання. З огляду на досвід кафедри ПІІТУ визначено, що педагогічні умови значно підвищують якість професійної підготовки майбутніх інженерів-програмістів.

The forming process of main pedagogical conditions that promote high quality training of future programmers in National Technical University "KhPI" is considered initially. The experience of pedagogical conditions implementation at the department of Software Engineering and Management Information Technologies (SEMIT) is presented. Teaching special disciplines in English and creation of English-speaking educational stream in the field of software engineering is shown to be one of the most significant pedagogical conditions that improves the quality of future programmers’ professional training. The other important pedagogical condition for training future programmers is stated to be a good command in computer applied mathematics – a discipline that was specially integrated into the curriculum. The next pedagogical condition is teachers’ work experience in real ITprojects. To implement the previous pedagogical condition the next one – the initiation of educational-scientific-productive complexes – was created. One of the important motivating pedagogical conditions is the creation of competitive environment among students – future programmers. The implementation of dual approach in educational process that is a combination of university training with a good manufacturing practice is considered to be one of the high-priority pedagogical conditions.
The formation and the experience of implementation of the pedagogical conditions of future engineer-programmers professional raining in National technical university "KhPI"
Keywords: конкурентне середовище; дуальний підхід у освіті; навчальний процес; інформаційні технології; програмування; pedagogical conditions; software engineering; competitive environment; dual approach in education